Modelling the orientation of accretion disks in quasars using H-alpha emission - Down, E; Rawlings, S; Sivia, D; Baker, J (2009)
Infrared spectroscopy of the H-alpha emission lines of a sub-sample of 19 high-redshift (0.8 < z < 2.3) Molonglo quasars, selected at 408 MHz, is presented. These emission lines are fitted with composite models of broad and narrow emission, which include combinations of classical broad-line regions of fast-moving gas clouds lying outside the quasar nucleus, and/or a theoretical model of emission from an optically-thick, flattened, rotating accretion disk. All bar one of the nineteen sources are found to have emission consistent with the presence of an optically-emitting accretion disk, with the exception appearing to display complex emission including at least three broad components. Ten of the quasars have strong Bayesian evidence for broad-line emission arising from an accretion disk together with a standard broad-line region, selected in preference to a model with two simple broad lines. Thus the best explanation for the complexity required to fit the broad H-alpha lines in this sample is optical emission from an accretion disk in addition to a region of fast-moving clouds. We derive estimates of the angle between the rotation axis of the accretion disk and the line of sight. A weak correlation is found between the accretion disk angle and the logarithm of the low-frequency radio luminosity. This is direct, albeit tenuous, evidence for the receding torus model. Velocity shifts of the broad H-alpha components are analysed and the results found to be consistent with a two-component model comprising one single-peaked broad line emitted at the same redshift as the narrow lines, and emission from an accretion disk which appears to be preferentially redshifted with respect to the narrow lines for high-redshift sources and blueshifted relative to the narrow lines for low-redshift sources.